Razvijanje in spodbujanje ustvarjalnosti z umetniškim delom pri mlajših učencih - Selaković, Kristinka (Revija za elementarno izobraževanje, 2017)
The aim of this experimental research was to examine the effectiveness and impact of active observation of the work of art by applying specially designed strategies, methods and procedures to the development of general artistic creativity in pupils. The research was conducted on a sample of 199 pupils (the experimental group consisted of 102 pupils, and the control group of 97 pupils) from two primary schools in Užice (Serbia). The conclusions indicate how important it is for children to access the work of art on a personal level, independently and through interaction, as well as to develop their own concepts.
Keywords: creativity; likovna vzgoja; umetniško delo; work of art; young pupils; opazovanje; ustvarjalnost; development program; museum; učenci; začetni pouk; osnovne šole